No evidence for tactile entrainment of attention - Pomper, Ulrich (Frontiers in Psychology, 2023)
Temporal patterns in our environment provide a rich source of information, to which endogenous neural processes linked to perception and attention can synchronize. This phenomenon, known as entrainment, has so far been studied predominately in the visual and auditory domains. It is currently unknown whether sensory phase-entrainment generalizes to the tactile modality, e.g., for the perception of surface patterns or when reading braille. Here, we address this open question via a behavioral experiment with preregistered experimental and analysis protocols. Twenty healthy participants were presented, on each trial, with 2 s of either rhythmic or arrhythmic 10 Hz tactile stimuli. Their task was to detect a subsequent tactile target either in-phase or out-of-phase with the rhythmic entrainment. Contrary to our hypothesis, we observed no evidence for sensory entrainment in response times, sensitivity or response bias. In line with several other recently reported null findings, our data suggest that behaviorally relevant sensory phase-entrainment might require very specific stimulus parameters, and may not generalize to the tactile domain.